Dispressive disorders and comorbidity : somatic illness vs. side effect - Uzun, Suzana (Array, 2009)
Schizophrenia often co-occurs with chronic medical illnesses. Beside comorbid somatic illness, somatic symptoms appear as a result of side effects of antipsychotics during treatment of psychotic disorders, which may lead to certain diagnostic problems in deciding regarding the origin of such symptoms (somatic illness vs. side effects). Genetic factors, sedentary life style, poor diet, risk behaviors and smoking are some important factors that contribute to such comorbidity. Side effects of antipsychotics may cause diagnostic problems in deciding regarding the origin of such symptoms (somatic illness vs. side effects) during treatment of psychotic disorders. It is important to recognize psychotic symptoms in patients with somatic illnesses, as well as somatic illness in patients primarily treated because of psychotic disorder